Applying a Critical Policy Lens to Contracting in Indigenous Mental Health: An Ethnographic Study with Urban Indigenous Providers - Josewski, Viviane; Morrow, Marina; Smye, Victoria; Lavoie, Josée; O'Neil, John; Mussell, William (The International Indigenous Policy Journal, 2023)
This article reports on the findings of a larger study that explored urban Indigenous providers’ experiences with contracting in mental health and addictions care. The study was undertaken with seven Indigenous and one non-Indigenous non-profit organizations based in diverse large and mid-size cities (off reserve) in British Columbia, Canada. Indigenous and critical theoretical perspectives provided the lens for this ethnographic inquiry. In-depth interviews were the primary data source. Participants’ narratives provide an account of the ideological embeddedness of contracting and how a New Public Management operates to perpetuate colonial power imbalances and structural barriers to culturally safe and equity-oriented care within urban Indigenous communities. Policy and practice implications for government funders are discussed.